"Subcritical" Glenoid Bone Loss Increases Redislocation Rates in Primary Arthroscopic Bankart Repair. Issue 7 (29th July 2014) - Shaha, James S.; Cook, Jay B.; Song, Daniel J.; Rowles, Douglas J.; Bottoni, Craig R.; Shaha, Steven H.; Tokish, John M.
Objectives: While bone loss is increasingly recognized as a risk factor for failure after arthroscopic stabilization, the precise definition of critical bone loss has not been defined. Additionally, there is no clarity on the amount of bone loss routinely present in patients presenting for primary arthroscopic stabilization of anterior glenohumeral instability. The purpose of this study is to report on the average bone loss measured in primary isolated Bankart reconstructions of the shoulder and to determine what amount of bone loss correlated to a recurrence of instability. Methods: This is a retrospective review of a consecutive series of 94 anterior instability patients (97 shoulders) who underwent arthroscopic labral repair at a single military institution by one of three fellowship trained orthopaedic surgeons. Data was collected on demographics and rate of redislocation as reported by the patient at the most recent follow-up. Glenoid bone loss was calculated from preoperative imagining using a "perfect-circle" technique. Patients were excluded if they had previously undergone any stabilization procedure. Results: The average age at surgery was 25.6 years (range, 16-42) with average follow-up of 36.8 months (range, 20-57). There were 5 females (5 shoulders) and 89 males (92 shoulders). The average bone loss in all patients was 14.4% (range, 0-34.7%). When analyzed based on the presence or absence of recurrence, there were 77 stable shoulders with no redislocations. In this group, the average bone loss was 14.5% (range, 0-33.3%) with a follow-up of 36.3 months (range, 20-57). There were 20 patients with recurrent dislocations who had an average of 20.8% (range, 0-33.3%) with a 39.1 month (range, 21-56) follow-up. There was a significantly greater amount of bone loss in those with redislocations (p=0.004). When further analyzed, there was a 95% likelihood of redislocation with 17.1% bone loss there was a 25% likelihood of redislocation with 7.0% bone loss. Conclusion: This study suggests that glenoid bone loss is a common finding in patients undergoing primary arthroscopic stabilization. Additionally, patients with "subcritical" bone loss of 17.1% are at a higher risk to have a recurrence than those with lesser amounts of bone loss. Patients with bone loss beyond this threshold should be counseled accordingly with consideration for alternative surgical procedures.